Cosmetic Surgery Art and Techniques - Shiffman, Melvin A.; Di Giuseppe, Alberto; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Cosmetic Surgery: Art and Techniques is an atlas of general cosmetic surgery that provides precise step-by-step descriptions of the full range of techniques, supported by photographs and illustrations of the highest standard. The book is comprehensive in its scope, covering the diverse procedures performed on the head and neck, breast, abdomen, buttocks, and extremities as well as other techniques such as labioplasty, penile enhancement, and total body lift. Risks and complications are fully explained, with clear advice on how to avoid and to treat them. All of the contributors are internationally recognized experts with extensive knowledge of their subject. This book will be of value to beginners, and experienced practitioners in not only cosmetic surgery but also plastic surgery, general surgery, oral maxillofacial surgery, neurosurgery, dermatology, otolaryngology, and ophthalmology.
Keywords: Medicine; Dermatology; Otorhinolaryngology; Head -- Surgery; Surgery; Medicine & Public Health; Plastic Surgery; Dermatology; Oral and Maxillofacial Surgery; Head and Neck Surgery; Otorhinolaryngology